Mimarlık Eğitiminde Peyzaj Tasarımı / Landscape Design in Architctural Education - Özdemir Işık, Buket; Sayitoğlu Taş, Çağla (Journal of History Culture and Art Research, 2018)
Abstract Collaboration among the professional disciplines has an important impact on the success of education and training. It is known that the architectural profession interacts with different professional disciplines at national and international universities that provide architectural education. These professions should be included in architectural education programs, especially because architecture is related to different disciplines such as civil engineering, interior architecture, landscape architecture, urban and regional planning. In this respect, design students studying in the field of architecture need to acquire interdisciplinary vocational education in order to develop their imagination, ability of thinking and to realize what they thinked. In this context, a survey was conducted with 61 students from the 4th grade students who took the Landscape Design course in the Architecture Department of Avrasya University, which provides architectural education. The students who attended the lessons were asked for their opinions about whether the lessons contributing their professional quality or not. Survey questions were analyzed by SPSS Statistics 24 analysis program. The students who participated in the survey stated that the course was especially helpful when designing the site plan, determining the site elevations and building entry-exit points. In addition, students stated that they would like to take the landscape design course in 2nd grade instead of taking in the 4th grade. Öz Mesleki disiplinler arasındaki ortak çalışmalar, eğitim öğretimin başarısı üzerinde önemli bir etkiye sahiptir. Mimarlık eğitimi veren ulusal ve uluslararası üniversitelerde de mimarlık mesleğinin farklı meslek disiplinleri ile etkileşim içerisinde olduğu bilinmektedir. Özellikle Mimarlığın, İnşaat Mühendisliği, İç Mimarlık, Peyzaj Mimarlığı, Şehir Bölge Planlama gibi farklı disiplinler ile ilişkili olmasından dolayı, bu disiplinlere dair mesleki bilgiler eğitim programlarında yer almalıdır. Bu açıdan mimarlık alanında eğitim öğretim gören tasarım öğrencilerinin, düşünme, düşünüleni görme ve hayata geçirme adına hayal güçlerini geliştirmek için disiplinler arası mesleki eğitimi almaları gerekmektedir. Bu bağlamda, bu çalışmada mimarlık eğitimi veren Avrasya Üniversitesi Mimarlık Bölümü, Peyzaj Tasarım dersini alan 4. Sınıf öğrencilerinden 61 kişi ile bir anket çalışması yapılmıştır. Dersi alan öğrencilerden ders kapsamında görüşleri istenmiş ve almış oldukları dersin, mesleki eğitimlerine katkısı olup olmadığı sorgulanmıştır. Anket soruları SPSS Statistics 24 analiz programı ile analiz edilmiştir. Ankete katılan öğrenciler dersin özellikle; vaziyet planı tasarlarken, arazi kotlarını ve bina giriş-çıkış noktalarını belirlerken yardımcı olduğunu ifade etmişlerdir. Ayrıca öğrenciler ankete vermiş oldukları cevaplarında 4. sınıfta almış oldukları Peyzaj Tasarım dersinin, eğitim öğretim yılları içerisinde 2. sınıfta almak istediklerini belirtmişlerdir.